Analisis strategi pengelolaan simpanan harian wadiah yad dhamanah dan simpanan harian idul fitri pada bmt sarana wiraswasta muslim dalam meningkatkan kepercayaan anggota - Marpaung, Reza Rahmad (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the management strategies of Wadiah Yad Dhamanah daily deposits and Idul Fitri daily deposits at BMT Sarana Wiraswasta Muslim in an effort to increase member trust. These two deposit products are superior because they have the largest number of members and play an important role in maintaining the liquidity and credibility of the institution. This study shows that the management strategies implemented by BMT Sarana Wiraswasta Muslim include fund transparency, excellent service based on a proactive approach in the market, a dual recording system (manual and digital), and flexibility in fund withdrawals and deposits. In addition, the funds collected are managed productively through sharia-based business capital financing such as mudharabah, musyarakah, and murabahah, which demonstrate the healthy operational performance of BMT. The implementation of this strategy not only strengthens the sense of security and certainty for members, but also increases their loyalty and participation in sharia financial activities. Thus, the management of Wadiah Yad Dhamanah and Idul Fitri daily deposits has proven to be a strategic instrument in building trust and strengthening the position of BMT as a credible, adaptive, and real-needs-oriented sharia microfinance institution.